2021
DOI: 10.1371/journal.pone.0259258
|View full text |Cite
|
Sign up to set email alerts
|

Understanding racial disparities in severe maternal morbidity using Bayesian network analysis

Abstract: Previous studies have evaluated the marginal effect of various factors on the risk of severe maternal morbidity (SMM) using regression approaches. We add to this literature by utilizing a Bayesian network (BN) approach to understand the joint effects of clinical, demographic, and area-level factors. We conducted a retrospective observational study using linked birth certificate and insurance claims data from the Arkansas All-Payer Claims Database (APCD), for the years 2013 through 2017. We used various learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Research has indicated that prepregnancy obesity is a potential limited driver of SMM disparities [44]. A Bayesian network analysis using an Arkansas All-Payer Claims Database (2013–2017) found that anemia and hypertensive disorders of pregnancy are important clinical comorbidities associated with SMM; both conditions were associated with Black race [45]. Mixed-effects linear regression model analysis (with adjustment for predefined covariates associated with blood pressure) of postpartum blood pressure trajectories among women with hypertensive disorders of pregnancy found that Black women had a less rapid decrease in postpartum blood pressure, which resulted in 68.1% of Black women compared with 51.4% of White women meeting the criteria for stage 1 or stage 2 hypertension by the end of a 6-week program [46].…”
Section: Risk Indicators For Obstetrical Disparitiesmentioning
confidence: 99%
“…Research has indicated that prepregnancy obesity is a potential limited driver of SMM disparities [44]. A Bayesian network analysis using an Arkansas All-Payer Claims Database (2013–2017) found that anemia and hypertensive disorders of pregnancy are important clinical comorbidities associated with SMM; both conditions were associated with Black race [45]. Mixed-effects linear regression model analysis (with adjustment for predefined covariates associated with blood pressure) of postpartum blood pressure trajectories among women with hypertensive disorders of pregnancy found that Black women had a less rapid decrease in postpartum blood pressure, which resulted in 68.1% of Black women compared with 51.4% of White women meeting the criteria for stage 1 or stage 2 hypertension by the end of a 6-week program [46].…”
Section: Risk Indicators For Obstetrical Disparitiesmentioning
confidence: 99%